Analisis Tindak Tutur Ilokusi pada Cuitan Akun Partai Gerindra di Media Sosial X - Aurelia Elfianda Salsabilla; Betania Tri Anggita; Cindi Nurhidayah; Mentari Nurlita Ramadhan (PRASASTI: Journal of Linguistics, 2025)
A communication interaction that uses speech in it can also be done through social media, one of which is platform X, where users can interact directly through comments, messages, and reactions to content published by others. Speech in these interactions always produces speech acts or speech events that can be analyzed. The object of research is the speech of Gerindra Party @Gerindra on social media X in the time span of March-April 2024 with discussion material in the form of the 2024 Election. In that time span, 44 data were found regarding illocutionary speech acts performed by the Gerindra Party @Gerindra. The data findings were analyzed using a qualitative description method with a listening, reading, and recording approach. Thus producing data in the form of speech acts carried out by the Gerindra Party @Gerindra, including the type of illocutionary speech acts with various subordinatives within it.